Sultan, Plantations, and Islam: Dynamics of Social-Political Life in East Sumatra (1900-1942) - Nabila Yasmin; Dody Syahputra Siregar (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2023)
This research explores the dynamics of social and political life in East Sumatra from 1900 to 1942, focusing on the role of the Sultan, plantations, and Islam. The research employed historical research methods in four steps: heuristic, criticism, interpretation, and historiography. Data were collected from relevant archives, books, articles, and reports on the research topic. The research is grounded in three hypotheses: 1) the Sultan and local elites played a significant role in the development of plantations in East Sumatra; 2) Islam served as a crucial factor in shaping political and social identities in East Sumatra; and 3) conflicts of interest between local elites and the colonial government influenced the dynamics of social and political life in East Sumatra during the studied period.